Humeral length versus femur length for estimating fetal age in the third trimester using ultrasound among saudi fetuses - Mahasin G Hassan (Journal of Medical Ultrasound, 2023)
Background: Ethnicity can influence organ measurements, so each ethnicity should provide normal references. The study was conducted to measure the normal ranges of humeral and femoral diaphysis lengths, to compare them during the third trimester of pregnancy in the Saudi population, and to identify their role in estimating fetal age. Methods: This cross-sectional study was conducted among 60 normal singleton pregnant females in the third trimester. The fetal humeral length (HL) and femur length (FL) were taken during ultrasound scanning for follow-up. The IBM Statistical Package for the Social Sciences Version 23 was used to summarize the data and to compare both the lengths with the last menstrual period (LMP) using Pearson's correlation. The comparison was considered statistically significant if P < 0.05. Results: The mean humeral and femoral diaphysis lengths ± standard deviations were 4.84 ± 1 cm and 5.54 ± 1.2 cm, respectively. A positive linear correlation was present between the length and LMP. The correlation of HL with LMP (r = 0.828) was higher than that of FL with LMP (r = 0.770). HL and FL were correlated. They showed a Pearson's coefficient of 0.941. The study revealed that gender does not affect fetal HL and FL. Conclusion: Normal reference ranges for femur and humeral diaphysis lengths during the third trimester were provided. The humerus can be used to assess fetal age. Humerus and femur were correlated to each other among Saudi fetuses. Another study with a larger sample size is recommended.